REFINEMENT OF THE STEEL FOR THE REINFORCEMENT CASTS - S. N. Primerov; V. V. Velmisov; E. S. Murzin; G. M. Slepnev (Литьë и металлургия)
The results of investigations of the steels of types 20L and 20GSL, modified by the silicon-free hardener AKTse complex, allows to recommend it for out-of-furnace treatment (modification) of such steels.